Anti-inflammatory Potential of Plants of Genus Rhus: Decrease in Inflammatory Mediators In Vitro and In Vivo – a Systematic Review - Rodríguez-Castillo, Alejandra Jazmín; Pacheco-Tena, César; Cuevas-Martínez, Rubén; Sánchez-Ramírez, Blanca Estela; González-Chávez, Susana Aideé (Planta Medica, 2025)
Plants from the Rhus genus are renowned for their medicinal properties, including anti-inflammatory effects; however, the mechanisms underlying these effects remain poorly understood. This systematic review, conducted following PRISMA guidelines, evaluated the anti-inflammatory effects of Rhus plants and explored their potential pharmacological mechanisms. A total of 35 articles were included, with the majority demonstrating a low-risk bias, as assessed using the SYRCLE tool. Rhus verniciflua, Rhus chinensis, Rhus coriaria, Rhus succedanea, Rhus tripartite, Rhus crenata, and Rhus trilobata were analyzed in the reviewed articles. In vitro studies consistently demonstrated the ability of Rhus plants to reduce key inflammatory mediators such as TNF-α, IL-1β, and IL-6. In vivo studies confirmed these effects in murine models of inflammation, with doses mostly of 400 and 800 mg/kg body weight, with no reports of toxicity. Fifty-four distinct inflammatory mediators were assessed in vivo; no pattern of mediators was identified that could elucidate the anti-inflammatory mechanisms of the action of Rhus in acute or chronic inflammation. The clinical trial reported anti-inflammatory effects in humans at 1000 mg/kg for 6 weeks. The review data on the Rhus-mediated reduction in inflammatory mediators were integrated and visualized using the Reactome bioinformatics database, which suggested that the mechanism of action of Rhus involves the inhibition of inflammasome signaling. These findings support the potential of Rhus plants as a basis for developing anti-inflammatory therapies. Further research is needed to optimize dosage regimens and fully explore their pharmacological applications.
Keywords: chronic inflammation; inflammasome; NLR signaling; IL-18; caspases; Rhus; Anacardiaceae